Delayed Hemolytic Transfusion Reaction due to Anti-Jkb: Case Report Highlighting the Importance of Early Blood Bank Consultation and Literature Review - Nguyen, MD, David M; Lee, MD, Hun J; Mirabella, MT(ASCP) SBB, Donna; Wu, MD, PhD, Ding Wen (North American Journal of Medicine and Science, 2010)
Delayed hemolytic transfusion reactions (DHTR) can be asymptomatic or mimic other conditions and may be misdiagnosed. Failure to recognize this entity could lead to inappropriate treatment and future transfusions reactions. Anti-JKa and anti-JKb are the most frequently encountered antibodies responsible for DHTR ac companied by intravascular hemolysis on rare occasions. The antibodies are often difficult to detect because of their transient nature and their frequent dosage effect. We report the case of a 40-year-old female with DHTR due to unexpected weakly reactive anti-JKb. The patient, with a medical history of hypertension, multiple transfusions, multiple abortions and vaginal bleeding due to uterine fibroids, presented to our emergency department complaining of back pain for four days and red-brown color urine for one day. Significant jaundice was noted on physical examination. Laboratory data showed low hemoglobin (Hb) (6.0g/dl) and increased creatinine (3.11 mg/dl). Differential diagnosis included hemolytic-uremic syndrome, hematuria caused by urinary tract calculi, and autoimmne hemolytic anemia. Significant hemolysis was observed in the patient’s blood sample. Further questioning elicited a recent blood transfusion seven days prior. Red cell antibody work-up at that time showed the presence of anti-K and anti-E. The patient was transfused 2 units of K and E antigen negative cross-match compatible packed red blood cells(PRBCs). Post-transfusion Hb was 8.8 g/dl and there were no signs of any immediate complication. Review of the recent history of blood transfusion and the current findings led to our strong suspicion of intravascular hemolysis. The patient was treated vigorously with fluids and intravenous diuretics. Stat tests subsequently confirmed the intravascular hemolysis. A ‘new’ request for blood transfusion was put on hold while an antibody workup was initiated. Red cell antibody work-up results confirmed the presence of anti-K and anti-E; the direct antiglobulin test (DAT) was negative. An eluate prepared from the patient’s red cells was non-reactive by indirect antiglobulin test. Additional samples were sent to a reference laboratory for further investigation of unexpected red cell antibodies. Results from the reference laboratory confirmed the anti-E and -K, and, in addition, a weak anti- JKb was identified in the plasma and eluate. Both of the prior transfused units were subsequently shown to be Jk(b+), adding further evidence that the anti- JKb is most likely the culprit of the DHTR. The patient was subsequently transfused with E-, K- and Jk(b-) PRBCs and her condition improved. This case emphasizes the central role of blood bank consultation for early treatment and diagnosis of DHTR and for the avoidance of incompatible blood component transfusion, thus minimizing the risks of morbidity and reduce the potential for mortality. It is our opinion that blood bankers should be consulted when patients have an acute drop in Hb following recent transfusions. Moreover, transfusion medicine should be part of medical school education and part of hospital grand round conferences, to raise clinicians’ awareness to improve recognition and reporting of DHTR so that timely diagnosis and treatment can be made.